Damage behavior of glass fiber reinforced plastic laminate and bovine-derived hydroxyapatite under low-velocity impact loading / Sadjad Naderi - Naderi, Sadjad (2015)
Modeling and simulation of mechanical behavior of biomaterials is a very important topic. Until now, there is no single simulation model valid for the wide range of biomaterial, which includes metal alloys, composite and porous materials. Therefore the objective of the present study is to develop a numerical model to cover evaluation of mechanical properties for two types of brittle biomaterials: hydroxyapatite (HA) as a porous material for hard tissue replacement and Glass Fiber Reinforced Plastic laminates (GFRPs) as a layered composite for dental applications. The plastic behavior of HA and the effect of porosity on the elastic-plastic behavior of HA have not been well studied and fully discovered. On the other hand, biomedical and industrial applications have focused to detect the effect of low-velocity impact on mechanical response of GFRP materials under fatigue loading. Finite element simulation models have been developed using MSC. MARC® to study on mechanical response of these brittle materials under impact and nanoindentation. The FE-inverse technique and semi-empirical method was introduced to infer the most suitable elastoplastic material model for HA. In addition, an effective approach is proposed to design irregular porous media using MATLAB code for HA with controllable pore shapes and distributions, without requiring any prior microscopic information. The impact damage process and contact stiffness for GFRP samples were investigated incrementally until when the composites were perforated. A Fatigue Damage index (FD) was introduced to capture the unique GFRP composite characteristics. Nanoindentation on HA and low-velocity impact, tensile static and fatigue tests on GFRP were performed to verify the numerical methods. The elastic-plastic material model has shown more reasonable mechanical behavior of HA. Proposed approach for generating irregular porous structures is easier and faster than the other existing approaches and constructed model appears more natural and realistic. The influence of low-velocity impact should be reflected in the design of GFRP structures. Even by increasing laminate thickness, the effect of impact is higher than the effect of thickness on the fatigue behavior of glass/epoxy laminates.